Brazilian guidelines for the management of psychomotor agitation. Part 2. Pharmacological approach - Baldaçara,Leonardo (2019)
Objective: To present the essential guidelines for pharmacological management of patients with psychomotor agitation in Brazil. Methods: This is a systematic review of articles retrieved from the MEDLINE (PubMed), Cochrane Database of Systematic Reviews, and SciELO databases published from 1997 to 2017. Other relevant articles in the literature were also used to develop these guidelines. The search strategy used structured questions formulated using the PICO model, as recommended by the Guidelines Project of the Brazilian Medical Association. Recommendations were summarized according to their level of evidence, which was determined using the Oxford Centre for Evidence-based Medicine system and critical appraisal tools. Results: Of 5,362 articles retrieved, 1,731 abstracts were selected for further reading. The final sample included 74 articles that met all inclusion criteria. The evidence shows that pharmacologic treatment is indicated only after non-pharmacologic approaches have failed. The cause of the agitation, side effects of the medications, and contraindications must guide the medication choice. The oral route should be preferred for drug administration; IV administration must be avoided. All subjects must be monitored before and after medication administration. Conclusion: If non-pharmacological strategies fail, medications are needed to control agitation and violent behavior. Once medicated, the patient should be monitored until a tranquil state is possible without excessive sedation. Systematic review registry number: CRD42017054440.